2016
DOI: 10.1093/cid/ciw557
|View full text |Cite|
|
Sign up to set email alerts
|

Forecasting Epidemiological Consequences of Maternal Immunization

Abstract: Background. The increase in the incidence of whooping cough (pertussis) in many countries with high vaccination coverage is alarming. Maternal pertussis immunization has been proposed as an effective means of protecting newborns during the interval between birth and the first routine dose. However, there are concerns regarding potential interference between maternal antibodies and the immune response elicited by the routine schedule, with possible long-term population-level effects.Methods. We formulated a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
2
25
0
1
Order By: Relevance
“…Our recent modelling study [12] identified a trade-off between the direct protection of infants via maternal immunisation and the reduced indirect effects of herd immunity, leading to a gradual increase in incidence among older age cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent modelling study [12] identified a trade-off between the direct protection of infants via maternal immunisation and the reduced indirect effects of herd immunity, leading to a gradual increase in incidence among older age cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent modelling study, we demonstrated that averting such an eventuality would require both prenatal and routine vaccination coverage to be sufficiently high [12]. Moreover, this study predicted that due to the slow rate of population turnover, such downstream increases in incidence would take decades to manifest.…”
Section: Maternal Immunisation Unknowns: Vaccine Interferencementioning
confidence: 90%
“…However, infectious disease researchers have made heavy use of information from social contact surveys. These are point-in-time (cross-sectional) household or individual surveys that collect detailed information on each respondent's daily contacts with other people who have specific age and gender attributes (Mossong et al, 2008;Bento and Rohani, 2016;Prem et al, 2017). Static contact surveys have proven to be useful for studying endemic diseases and seasonal diseases that occur fairly reliably in a population because sudden disruptions of behavior are not expected.…”
Section: Pre-covid Epidemiological Research On Mobilitymentioning
confidence: 99%
“…Specific models have been designed for diseases such as measles,[ 7 ] rubella, chickenpox,[ 8 ] dengue fever,[ 9 ] whooping cough,[ 10 ] smallpox,[ 11 ] malaria,[ 12 ] HIV/AIDS [ 13 ] and others. [ 14 ] Most models take the basic reproduction number R0 of the causative agent, defined as the threshold quantity that determines when an infection can invade and persist in a new host population, as one of the main assets.…”
Section: Introductionmentioning
confidence: 99%